Women and the Sciences: A Feminist Poststructuralist Analysis of the Marquise du Châtelet’s (Revista Brasileira de Pesquisa em Educação em Ciências, 2023)
In the 1730s, there were many doubts about the nature of heat and fire. In view of this, the Academy of Sciences in Paris proposed a prize for the dissertation that brought a solution to this issue. In a context in which women's education was directed solely at the domestic sphere, Marquise Émilie du Châtelet submitted her Dissertation on the nature and propagation of Fire and overcame the obstacles that limited women's participation in Science. Academia managed to prevent her physical presence, but her name and her ideas transcended the barriers of the Enlightenment and the determinist thought of that period, and she became a recognized, published and recommended woman. In this work, we present this character and an analysis of her work on Fire. In order to do so, this research relied mostly on bibliographical information, which implied the search and analysis of primary, secondary and tertiary sources for the study of Du Châtelet’s Dissertation. For the analysis of primary and secondary sources, we relied on a poststructuralist feminist perspective for the understanding of the marquise's role in her time. In this way, in a poststructuralist feminist reading, the marquise is an example that there are no biological, structural and temporal limits that justify the ideological barriers used to essentially support the participation of women in scientific fields. The fact of being a woman was decisive for her historiographic erasure, denouncing a deliberate choice made by men during centuries of exclusion and silencing of women.